INCREASING CUSTOMER LOYALTY THROUGH PRODUCT AND SERVICE IMPROVEMENT: A CASE OF WAROENG KOE RESTAURANT JAKARTA - Aliya, Qonita Himmatul; Lestari, Yuliani Dwi (Journal of Business and Management, 2017)
Abstract. Background: The purpose is to know the gap between expectation and perception of customer to make satisfaction level. Methods: This study was used quantitative approach using SERVQUAL framework and distributing a questionnaire survey to 65 respondent of Waroeng Koe customer. This research use 2 session of questionnaire that are expectation session and perception session that conducted in waroeng koe. Results:  The fundamental result of this research, there are gaps for all the dimension and it is negative. The widest gap is in responsiveness followed by tangible dimension. But in the improvement priority, the first and second priority is responsiveness and assurance dimension. Conclusion: Waroeng koe restaurant should focus on these two dimension responsiveness and assurance to make the improvement for these.  Keywords:  Customer Satisfaction, SERVQUAL, Restaurant, Customer GAP, Product and Service